Structural Phylogenomics: Selection Pressure Suggests the Functionally Important Residues Encoded by Cisplatin Resistance Related 9 Gene - Saadia Shakir; Waqas Ahmed Waseem; Syed Khaqan Hasan; Muhammad Munir; Muhammad Rafiq Khanani; Mushtaq Hussain (Journal of the Dow University of Health Sciences, 2015)
Cisplatin Resistance Related 9 gene, CRR9, contributes towards the efficacy of the chemotherapeutic drug namely cisplatin. Genetic studies have established the association between CRR9 gene mutations and several cancers, but the structure-function aspects of the encoded protein remains largely unaddressed. In the present study, we have constructed a consensus phylogenetic tree of the CRR9 gene using maximum likelihood method after 1000 bootstrap replicates. Multiple sequence alignment of the selected orthologs was undertaken and important variations were analyzed with reference to the clade segregations and spatial locations in the constructed protein structure models. The topology of the phylogenetic tree appears in line with the established phylogenetic relationship of the mammalian lineage. The protein models of selected mammalian representatives suggest strong uniformity as Root Mean Square Deviation which varies from 0.03Å to 0.14Å. Both the DAS server and protein structure suggest the presence of two novel transmembrane regions ranging from Val461 to Ala483 and Thr490 to Tyr506. Multiple sequence alignment of the protein showed primate specific amino acid substitutions. Importantly, these variations are mostly situated in the core part of the protein structure implying their structural and/or functional significance.